Investigating Feasibility of C. I. direct Yellow 50 dye Degradation and Detoxicification in Synthetic Aquatic Solution Effluent by UVA/TiO2 Nanophotocatalytic process using Daphnia magna - Feizollah Dinarvand; Nematollah Jaafarzadeh; Mehdi Ahmadi Moghadam; Mohammad Bagher Miranzadeh; Nezam Mirzaei (Journal of Water and Environmental Nanotechnology)
Introduction and Aims: Compounds containing dye are toxic, carcinogenic and mutagenic for aquatic organisms and lead to mutagenicity, carcinogenicity, and dysfunction of human beings’ kidney, liver, brain, reproductive system and central nervous system. Advanced oxidation processes can remove pollutants faster than other processes due to active hydroxyl radical production. This study was aimed at investigating feasibility of dye removal using UVA/TiO2 process.Materials and methods: This study was done in a batch reactor and the effects of initial dye concentrations, TiO2 nanoparticles dosage, time, pH and interference compounds on efficiency of dye degradation was investigated. The Daphnia Magna as bioassay test and biodegradability index (BOD5/COD rate) were used for detoxification assessment.Results: The D.Y 50 dye effluent degradation at pH 2, 20 mg/l initial dye concentration and 1 g/l TiO2 catalyst was (lnC0/C= 1.4), (lnC0/C= 3) and (lnC0/C= 2.9) respectively. Dye removal rate by 50 mg/l COD concentration was (88%), Daphnia Magna mortality rate after maximum contact time (96 h) decreased from 96.7% to 43.3% and biodegradability index increased from 0.25 to 0.68.